Composites of Polymer Hydrogels and Nanoparticulate Systems for Biomedical and Pharmaceutical Applications - Fuli Zhao; Dan Yao; Ruiwei Guo; Liandong Deng; Anjie Dong; Jianhua Zhang (Nanomaterials, 2015)
Due to their unique structures and properties, three-dimensional hydrogels and nanostructured particles have been widely studied and shown a very high potential for medical, therapeutic and diagnostic applications. However, hydrogels and nanoparticulate systems have respective disadvantages that limit their widespread applications. Recently, the incorporation of nanostructured fillers into hydrogels has been developed as an innovative means for the creation of novel materials with diverse functionality in order to meet new challenges. In this review, the fundamentals of hydrogels and nanoparticles (NPs) were briefly discussed, and then we comprehensively summarized recent advances in the design, synthesis, functionalization and application of nanocomposite hydrogels with enhanced mechanical, biological and physicochemical properties. Moreover, the current challenges and future opportunities for the use of these promising materials in the biomedical sector, especially the nanocomposite hydrogels produced from hydrogels and polymeric NPs, are discussed.